On enhancing the reliability of digital microfluidic biochips (DMFB) through electrode cells health classification - Sheikh, M.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
Reliability of digital microfluidic biochips (DMFB) emerges to be a critical issue, as they are becoming a popular alternative for laboratory experiments like DNA analysis, immunoassays and safety critical clinical diagnostics. To improve DMFB reliability, the key is to know the possible points of failure of its electrode cells. In this paper, a novel test methodology is introduced to monitor the health of the DMFB by classifying its individual cells into weak, faulty and fault-free. The emphasis is on identifying physically degraded cells in the DMFB array and reducing their over-use, thus saving those cells from becoming faulty during operation. Degradation in cell health is measured by the change in its capacitance via a capacitance measurement circuit that can be integrated with the DMFB. The paper also presents the circuit to classify the cells as weak, faulty and fault free, implemented using 180nm technology. Â© 2015 IEEE.